Graded activation of mutant K41C-KCNE1:KCNQ1 channel complexes by mefenamic acid - Yundi Wang; Magnus Chan; Marc Pourrier; Jodene Eldstrom; David Fedida (Channels)
The IKs current formed by the co-assembly of KCNE1 and KCNQ1 plays an important role in cardiac repolarization. Mefenamic acid, an NSAID, is known to enhance IKs currents and has in turn been suggested as a therapeutic starting point for the development of compounds for the treatment of long QT syndrome. Our previous examinations of mefenamic acid’s action revealed that residue K41 on KCNE1 was critical for mefenamic acid’s activating effect on fully KCNE1 saturated, and partially saturated IKs channel complexes. The present study extends our previous work by incorporating the K41C-KCNE1 mutation into individual subunits to destabilize local mefenamic acid binding and explore how many of the remaining mefenamic acid-bound WT KCNE1-KCNQ1 subunits are required to support the activating action of the drug. Our results show that the potency of mefenamic acid action is reduced by the presence of K41C-KCNE1 subunits in a graded and stoichiometric, but non-linear manner. Modeling results are consistent with the idea that WT IKs subunits, in the presence of mefenamic acid, precede activation of K41C-IKs subunits due to their augmented voltage sensor kinetics.